The YOUth study: Rationale, design, and study procedures. (December 2020) - Onland-Moret, N. Charlotte; Buizer-Voskamp, Jacobine E.; Albers, Maria E.W.A.; Brouwer, Rachel M.; Buimer, Elizabeth E.L.; Hessels, Roy S.; de Heus, Roel; Huijding, Jorg; Junge, Caroline M.M.; Mandl, René C.W.; Pas, Pascal; Vink, Matthijs; et al.
Highlights: This article describes the rationale, design, and procedures of the YOUth cohort. YOUth is set up to investigate what drives the development of social competence and self-regulation in children. YOUth specifically investigates the role of neurocognitive development in child development. YOUth has a flexible longitudinal design with repeated measurements throughout childhood, starting prenatally. Abstract: Behavioral development in children shows large inter-individual variation, and is driven by the interplay between biological, psychological, and environmental processes. However, there is still little insight into how these processes interact. The YOUth cohort specifically focuses on two core characteristics of behavioral development: social competence and self-regulation. Social competence refers to the ability to engage in meaningful interactions with others, whereas self-regulation is the ability to control one's emotions, behavior, and impulses, to balance between reactivity and control of the reaction, and to adjust to the prevailing environment. YOUth is an accelerated population-based longitudinal cohort study with repeated measurements, centering on two groups: YOUth Baby & Child and YOUth Child & Adolescent. YOUth Baby & Child aims to include 3, 000 pregnant women, their partners and children, wheras YOUth Child & Adolescent aims to include 2, 000 children aged between 8 and 10 years old and their parents. All participants will be followed for at least 6 years, and potentially longer. In this paper we describe in detail the design of this study, the population included, the determinants, intermediate neurocognitive measures and outcomes included in the study. Furthermore, we describe in detail the procedures of inclusion, informed consent, and study participation.